Contribution to the knowledge of the genus Agalope Walker from mainland China, with descriptions of four new species (Lepidoptera, Zygaenidae, Chalcosiinae) - Huang, Si-Yao; Zhu, Li-Juan; Chen, En-Yong; Xu, Yong-Qiang; Wang, Min; Fan, Xiao-Ling; Pan, Zhao-Hui; Espeland, Marianne (Zootaxa, 2022)
New information of the genus Agalope Walker, 1854 from mainland China is presented. Three new species of the Agalope pica species-group are described: A. haoi S.-Y. Huang sp. n. from Weixi County, Yunnan, A. chayuensis S.-Y. Huang & Pan sp. n. from Chayu County, Southeastern Xizang and A. owadai S.-Y. Huang sp. n. from Bomi and Jiali Counties, Southeastern and Eastern Xizang. The little-known Agalope aurelia Oberthür, 1923 and A. lucia Oberthür, 1923 were rediscovered, with the male of the latter reported for the first time. Based on the newly discovered male, Agalope lucia is found to be a close relative of A. dejeani, hence it is excluded from the A. pica species-group and transferred to the A. bieti species-group. A new species of the Agalope hyalina species-group is also described: A. jianqingi S.-Y. Huang sp. n. from Pianma, Western Yunnan. Adults and genitalia of the aforementioned and related taxa are illustrated. An updated checklist of the genus is also provided.